1992
DOI: 10.2527/1992.7041060x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selection methods at the same level of inbreeding

Abstract: Animal geneticists predict higher genetic responses to selection by increasing the accuracy of selection using BLUP with information on relatives. Comparison of different selection methods is usually made with the same total number tested and with the same number of parents and mating structure so as to give some acceptable (low) level of inbreeding. Use of family information by BLUP results in the individuals selected being more closely related, and the levels of inbreeding are increased, thereby breaking the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
0
13

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 11 publications
8
49
0
13
Order By: Relevance
“…In this study, F was calculated using the Meuwissen and Luo (1992) algorithm. Previous studies have shown that increase in average inbreeding coefficient can be used as a measure of reduction in genetic diversity (Quinton et al, 1992;Wang, 1997). The rate of inbreeding (DF ) is the relative increase in inbreeding coefficient of individuals per generation.…”
Section: Ancestral Contributionmentioning
confidence: 99%
“…In this study, F was calculated using the Meuwissen and Luo (1992) algorithm. Previous studies have shown that increase in average inbreeding coefficient can be used as a measure of reduction in genetic diversity (Quinton et al, 1992;Wang, 1997). The rate of inbreeding (DF ) is the relative increase in inbreeding coefficient of individuals per generation.…”
Section: Ancestral Contributionmentioning
confidence: 99%
“…O aumento na intensidade de seleção, por exemplo, provoca decréscimo no tamanho efetivo da população e, conseqüentemente, na resposta à seleção. Da mesma forma, o aumento na acurácia da seleção pelo uso de índices de família ou BLUP também reduz o tamanho efetivo da população, ocasionando aumento mais rápido na taxa de endogamia (Quinton et al, 1992;Quinton & Smith, 1995).…”
Section: Introductionunclassified
“…Segundo Caballero (1994), o tamanho efetivo da população é a chave no processo evolutivo e na genética quantitativa, pois fornece a medida da taxa de oscilação genética e endogamia numa população. Quinton et al (1992) avaliaram métodos de seleção, sob mesma taxa de endogamia, e concluíram que a seleção com base no fenótipo apresentou melhores respostas do que os outros métodos de seleção estudados, quando o objetivo foi manter baixa a taxa de endogamia (1% por geração).…”
Section: Introductionunclassified
“…Segundo Caballero (1994), o tamanho efetivo da população é a chave no processo evolutivo e na genética quantitativa, pois fornece a medida da taxa de oscilação genética e endogamia numa população. Quinton et al (1992) avaliaram métodos de seleção, sob mesma taxa de endogamia, e concluíram que a seleção com base no fenótipo apresentou melhores respostas do que os outros métodos de seleção estudados, quando o objetivo foi manter baixa a taxa de endogamia (1% por geração).Segundo Lynch & Walsh (1999), o BLUP (melhor predição linear não-viesada) pode ser usado em situações de grande volume e complexidade das informações de pedigree, pois, quando tal método é utilizado para estimar o valor genético de um indivíduo, todas as informações disponíveis de seus parentes conferem à …”
unclassified